In Vitro Brassica Genotypes Growth Evaluation against NaCl Salt Stress: Brassica Genotypes against Salt Stress (Biological Sciences - PJSIR, 2019)
A hydroponic study was conducted to see the performance of fifteen Brassica genotypes (BARD-I, Sultan Raya, 19-H, Shiralle, Dunkled, 85-508, Toria, 85-499, BSA, 85-397, 85-500, 85-497, 85-5001, CON-I, and Jewel) for their salt tolerance. Four levels of NaCl (0, 30, 60 and 90 mM/L) were developed. One week old two healthy seedlings of each Brassica genotypes were transplanted in holes of thermopole sheet floating over a 200 mL capacity container having half strength Hoagland solution. Increasing the NaCl salinity significantly reduced the shoot and root dry weight of all Brassica genotypes. On an average, about 47% reduction in shoot dry weight was observed under higher salinity level (90 mM/NaCl). Although, all the genotypes differed among themselves in ability to tolerate salinity however, ranking order of genotypes showed that Sultan Raya performed well followed by BARD-I than rest of the genotypes. Genotype 85-500 produced comparatively the least shoot and root dry weights and accumulated more Na+, less K+ and Ca+2 than rest of the genotypes. The reverse was true for Sultan Raya and BARD-I. The farmers could be benefitted through growing the selected comparatively more tolerant genotypes which could grow and survive under salt stress conditions rather than complete crop failure.